2022
DOI: 10.1136/bmj-2021-069369
|View full text |Cite
|
Sign up to set email alerts
|

Normalising menopause

Abstract: Martha Hickey and colleagues argue that social and cultural attitudes contribute to the varied experience of menopause and that medicalisation fuels negative perceptions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
(35 reference statements)
0
15
0
1
Order By: Relevance
“…Menopause is a natural life event and certainly in the UK, is in danger of becoming overmedicalised and being defined as a disease which needs treatment. 12 The majority of the women in our survey, when asked how they felt about no longer having periods, felt happy. When asked how they felt about their feeling towards the menopause before they went through it, 53.8% said they had no strong views and the second most common answer was that they were accepting of it (18.0%).…”
Section: Women's Attitudes Towards the Menopausementioning
confidence: 84%
See 1 more Smart Citation
“…Menopause is a natural life event and certainly in the UK, is in danger of becoming overmedicalised and being defined as a disease which needs treatment. 12 The majority of the women in our survey, when asked how they felt about no longer having periods, felt happy. When asked how they felt about their feeling towards the menopause before they went through it, 53.8% said they had no strong views and the second most common answer was that they were accepting of it (18.0%).…”
Section: Women's Attitudes Towards the Menopausementioning
confidence: 84%
“…9 It has been shown that women with more negative attitudes towards the menopause in general report more symptoms during the perimenopause. 11,12 This study was part of an online survey done by Harper et al exploring attitudes and knowledge of women over 40 years about the menopause and the perimenopause data has been reported. 6 The aim of this paper was to explore postmenopausal women's attitudes and feelings towards the menopause and to gain an insight into their lived experiences with the aim of helping develop educational resources.…”
Section: Introductionmentioning
confidence: 99%
“…We also caution against the usage of this recommendation as a pretext for unnecessary medicalisation of what fundamentally constitutes a special situation in women’s life course, thereby limiting women’s ability to experience liberation from presentations and consequences of menstruation, pregnancy and contraception, in addition to adding up to medicines and cost related anxieties. 8 Rather, we urge that the health care systems be re-oriented to embrace both the challenges and opportunities that come with addressing menopausal women’s needs. Such an inclination would encourage women’s passage through menopause naturally by preventing unnecessary medication and the unintended effects that follow, and promoting balanced diet, exercise and related behaviours responding not only to bodily changes but also a transitioning social role of menopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…El descenso estrogénico puede originar síntomas vasomotores y sequedad vaginal para los cuales los estrógenos, con o sin progestágenos, al igual que la tibolona 137 se han mostrado eficaces 135 , 138 , 139 . No existen datos para asociar el climaterio con las alteraciones del estado del ánimo 140 , estando más en relación con padecimientos depresivos previos, acontecimientos vitales estresantes 141 o con actitudes negativas sobre la menopausia 142 , 143 , por lo que no se justifica el tratamiento ni la prevención de los mismos con terapia hormonal 144 . No se ha demostrado que el tratamiento hormonal oral o transdérmico sea eficaz para prevenir infecciones urinarias 145 , ni tratar la incontinencia urinaria 146 , 147 , o prevenir la enfermedad cardiovascular si se administra antes de los 60 años 148 , 149 , 150 , como sugerían algunos autores 151 .…”
Section: Actividades Preventivas En La Menopausia Osteoporosisunclassified